2013
DOI: 10.1088/0957-4484/24/38/382001
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic electronics: materials, devices and applications

Abstract: In this paper, the recent progress of synaptic electronics is reviewed. The basics of biological synaptic plasticity and learning are described. The material properties and electrical switching characteristics of a variety of synaptic devices are discussed, with a focus on the use of synaptic devices for neuromorphic or brain-inspired computing. Performance metrics desirable for large-scale implementations of synaptic devices are illustrated. A review of recent work on targeted computing applications with syna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
871
0
7

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,088 publications
(924 citation statements)
references
References 123 publications
11
871
0
7
Order By: Relevance
“…Because of the ability to continuously change the resistance in response to the input electrical signal (by analogy with a synapse), the memristive devices are considered as a basis of the electronic neuromorphic systems designed using the principles of biological neural structures [7][8][9][10]. It has already been shown that memristive nanostructures can mimic such a key function of the biological synapse as synaptic plasticity, the shortterm and long-term facilitation/depression and spiketiming-dependent plasticity (STDP).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the ability to continuously change the resistance in response to the input electrical signal (by analogy with a synapse), the memristive devices are considered as a basis of the electronic neuromorphic systems designed using the principles of biological neural structures [7][8][9][10]. It has already been shown that memristive nanostructures can mimic such a key function of the biological synapse as synaptic plasticity, the shortterm and long-term facilitation/depression and spiketiming-dependent plasticity (STDP).…”
Section: Introductionmentioning
confidence: 99%
“…Previous XPS studies of CeO x suggest that the Ce 3d XPS core-level spectrum has three-lobed envelops (which are located at around 882-890 eV, 895-910 eV and 916 eV) that originate from the different final states of mixed valency [1][2][3]. In Ce 3d spectrum, the u''' (v '''), u'' (v'') and u (v) denote the Ce 4+ final states and correspond to Ce 3d 9 4f 0 O 2p 6 , Ce 3d 9 4f 1 O 2p 5 and Ce 3d 9 4f 4 O 2p 4 respectively for Ce3d 3/2 and Ce3d 5/2 . The Ce 3+ final states in Ce 3d spectrum correspond to 3d 9 4f 1 O 2p 5 and 3d 9 4f 2 O 2p 4 and are labeled as u' (v') and u o (v o ) in the XPS spectrum.…”
Section: X-ray Photoelectron Spectroscopy (Xps) Studiesmentioning
confidence: 99%
“…In general, memristors offer non-linear switching characteristics, and materials and process compatibility with advanced silicon manufacturing. These attributes have spurred the exploration of memristors as synaptic devices for realizing spike-based hardware learning systems that are capable of processing unstructured, temporal data [5][6][7][8][9][10]. However, for memristor-based technologies to be viable, the device should exhibit several key characteristics.…”
mentioning
confidence: 99%
“…Brain-inspired computing is an emerging field, which can achieve artificial intelligence by means of simulating neural network of human's brain, as it can extend the capabilities of information technology beyond the Von Neumann paradigm [1,2]. In biological systems, synapses are the bridges between neurons [1,3], and they can change their intensity to enhance (synaptic potentiation) or weaken (synaptic depression) the connection between two neurons.…”
Section: Introductionmentioning
confidence: 99%